Historical aspects of aseptics and antiseptics - A. M. Morozov; A. N. Sergeev; S. V. Zhukov; A. M. Varpetyan; T. S. Ryzhova; M. M. Muravlyantseva; V. T. Jafarov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2021)
Relevance. For many centuries, infectious complications have been one of the most pressing problems of surgical practice. In modern medicine, a wide range of aseptic and antiseptic methods is presented, which, without harm to the body, can destroy pathogenic microorganisms and prevent the development of purulent complications that significantly aggravate the patient's condition and increase the duration of treatment. However, this was not always the case. In the era of the formation of surgery, interventions in a significant majority of cases ended with the development of purulent and septic complications, which inevitably led to death.The purpose of this study was to study the main points that play a key role in the history of the formation of modern asepsis and antiseptics.Material and methods. In the course of the study, an analysis of domestic and foreign literature on the history of the development of aseptics and antiseptics was carried out. When compiling the work, the biographical method of historical research was used. Articles and historical sketches of the period of the described events were also used as materials.Results. The formation of the principles of asepsis and antisepsis is a long historical process in which many of the greatest minds of mankind have been involved. At the same time, like the development of any scientific worldview, the development of asepsis and antiseptics was based on previous knowledge, as well as on knowledge obtained, mainly empirically. From time immemorial, physicians have already had an idea of the antibacterial properties of a number of compounds. The first mentions of attempts to prevent contamination of wounds and their disinfection date back to the time of Hippocrates. In the Middle Ages, for the purpose of disinfecting wounds, cauterization with a red-hot iron and boiling oil was widely used. From the middle of the 18th century, the first antiseptics entered the practice of surgeons. From the middle of the 19th century, a significant contribution to the development of asepsis and antiseptics was made by the Russian surgeon N.I. Pirogov, and his follower N.V. Sklifosovsky. A breakthrough in the development of asepsis and antiseptics in the late 19th – early 20th centuries was the scientific discovery of the French scientist Louis Pasteur, who proved that the processes of fermentation and decay are caused by microorganisms. This discovery formed the basis of J. Lister's antiseptic method. At the end of the 19th century, E. von Bergmann developed the aseptic method. One of the last significant events in the history of antiseptics was A. Fleming antibiotics.Conclusions. Thanks to the work of great scientists and doctors, there are many life-threatening postoperative complications that claimed the lives of many people, if they did not remain in the past, then their incidence and intensity of manifestations have noticeably decreased, and asepsis and antiseptics have become an integral component of surgical practice.